If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 6(-4) = 1 Multiply 6 * -4 -1x + -24 = 1 Reorder the terms: -24 + -1x = 1 Solving -24 + -1x = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + -1x = 1 + 24 Combine like terms: -24 + 24 = 0 0 + -1x = 1 + 24 -1x = 1 + 24 Combine like terms: 1 + 24 = 25 -1x = 25 Divide each side by '-1'. x = -25 Simplifying x = -25
| 4x+8=6x+2 | | 28/16=x/12 | | 9x+4=-5+2x+23 | | 9x+4=-52x+23 | | 28x=192 | | 8-7x-3=-26+4x-13 | | 7xy+3y=-22 | | -6a=-4 | | 5x+23=3+8x-7 | | 6x+30y=238 | | 1e+8=2e-12 | | 6x-1=4x+33 | | (4-6x)/(x^2+3x-10)=-2 | | 2x+18y=138 | | -3x-8=7x+22 | | 360h=3290 | | x^2/(x+1)/(x-1)=-2 | | 35=x | | 13y+22= | | 1/2(35)=x | | 63-7x=21x+20 | | 81-2x=-11x | | 0.4x+7.6=6.2 | | 0.9(x+60)+0.1x=79 | | 6x-1=5x+4 | | -10n=2/3 | | (2x-4)/(x+5)=-3 | | -11-4=-9/4n | | (2x-4)/(x+5)=1 | | -20-(-46)=x/12 | | (x+2)/(3-x)=3 | | 15d=300 |